2020
DOI: 10.1109/access.2020.2999903
|View full text |Cite
|
Sign up to set email alerts
|

Similarity-Based Models for Day-Ahead Solar PV Generation Forecasting

Abstract: Accurate forecasting of solar photovoltaic (PV) power for the next day plays an important role in unit commitment, economic dispatch, and storage system management. However, forecasting solar PV power in high temporal resolution such as five-minute resolution is challenging because most of PV forecasting models can only achieve the same temporal resolution as their predictors(i.e., weather variables), whose temporal resolution is usually low (i.e., hourly). To address this challenge, similaritybased forecastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The dataset used in this proposed model is extracted from various Machine Learning algorithms. Sangrody et al [15] had designed a similarity based model for forecasting the day ahead solar photo voltaic generation. The author proposed three forecasting models namely basic Similarity Based Forecasting Model (SBFM), categorized Similarity Based Forecasting Model (SBFM) and hierarchical Similarity Based Forecasting Model (SBFM).…”
Section: Recent Research Resultsmentioning
confidence: 99%
“…The dataset used in this proposed model is extracted from various Machine Learning algorithms. Sangrody et al [15] had designed a similarity based model for forecasting the day ahead solar photo voltaic generation. The author proposed three forecasting models namely basic Similarity Based Forecasting Model (SBFM), categorized Similarity Based Forecasting Model (SBFM) and hierarchical Similarity Based Forecasting Model (SBFM).…”
Section: Recent Research Resultsmentioning
confidence: 99%
“…In [14], models are proposed for predicting the power of PV with a resolution of 5 minutes using weather variables with a resolution of 1 hour, which improves the accuracy of the forecast.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Based on correlations among weather variables [9], [14], Marquez et al [15] concludes that sky (cloud) cover, (probability of) precipitation, (maximum and minimum) temperatures, and cos(ߠ ௌ ) are overwhelmingly and critically important to enhance the forecasting accuracy. Excluding sky cover from a list of commonly available weather data, Sangrody et al [16] and Qing et al [17] found that temperature and humidity had the strongest influence on accuracy of irradiance forecasts.…”
Section: Introductionmentioning
confidence: 99%